Patrimônio biocultural e as práticas haliêuticas em uma comunidade tradicional: uma abordagem etnoecológica - Santos, Lucas Silva Pachêco dos (2025)
Artisanal fishing, practiced for centuries, is essential for the food security and culture of traditional communities. In the Northeast of Brazil, the quilombola community of fishermen in Santiago do Iguape, Cachoeira (BA), is an example of a people whose subsistence is linked to this activity, despite conflicts and unhealthy conditions. Given this scenario, this dissertation sought, through an etic-emic approach, to understand the local fishing system, socioenvironmental challenges, the role of women, and the interest of young people in the continuity of this culture. The research, based on semi-structured interviews with 49 fishermen, an online questionnaire with 56 young people, and participant observations, revealed that the community possesses vast knowledge about the ecosystem and the environmental impacts that affect it. Among the main problems are the impacts generated by the Pedra do Cavalo Hydroelectric Plant, the use of fine-mesh nets, contamination by domestic and industrial effluents, in addition to the use of explosives that intensify the destruction of fishing resources. A critical point evidenced was the risk of biocultural erosion. The results indicate a significant reduction in youth labor in these activities, with 75% of the young people interviewed not intending to continue in the profession. This devaluation is largely due to difficult working conditions and a lack of incentives, which fragments and threatens the transmission of traditional knowledge. However, the research also highlights the strength of the women fishers, who play a central role in maintaining these practices. They represent a significant part of the workforce, organize to fight for their rights, and actively participate in the management of fishing territories. The results point to the urgency of joint actions among the community, public authorities, and civil society organizations to ensure the continuity of artisanal fishing. As a suggestion, we propose the implementation of environmental education programs in schools that highlight fishing not only as an economic activity but as a fundamental element of local culture and identity. Only with better working conditions and greater appreciation can young people become the guardians of this historical, social, and cultural heritage.